Pengaruh Berkumur Air Rebusan Cabe Jawa Terhadap Ph Saliva - Mohamad Andika Suryawan; Prasko Santosa; Hermien Rumbiastuti (Jurnal Kesehatan Gigi (Dental Health Journal), 2014)
Background. Mouth ferment carbohydrates to lactic acid which will lower the acidity of the mouth, resulting in tooth enamel demineralization. To prevent a decrease in the pH of saliva can be done chemically. In this study, the water boiled chili Java ( Pipper Retrofractum Vahl ) as an alternative solution pH of saliva is one component to affect the pH of the mouth. Pathogenic bacteria contained in the cavity mouthwash because essential oils are able to prevent the decrease in salivary pH by inhibiting the growth of pathogenic bacteria, reduce the viscosity and increase the salivary flow rate, as well as inhibit pellicle formation. Objectives Knowing the effect of alcohol chili Java ( Pipper Retrofractum Vahl ) on the pH of saliva. Methods The study design of clinical trials conducted by the pretest - posttest group design. The sample was 02-03 elementary students Pedurungan Kidul, Pedurungan Kidul, Semarang, 43 respondents treatment groups. Salivary pH was measured using a pH of 0.0 to 14.0 scale check of the GC. Data were analyzed with Spiro-Wilk test followed by Wilcoxon Signed Ranks Test Test Test. Result Wilcoxon Signed Ranks Test generate a significance value of P 0.05. There is a significant difference ( p 0.05 ) in the treated group compared with the group before after treatment. The results of this study indicate that the pH value of saliva in the treatment group (median = 7.50 ) higher than the control group (median = 7.30 ). Conclusion Giving Java chili cooking water can increase the pH of saliva. There are different in salivary pH values were significant between the groups before treatment and intervention group, where in the pH value of saliva in the group after the intervention group was higher than before treatment.